THE EFFECTS OF TESTOSTERONE THERAPY COMBINED WITH SWIMMING EXERCISE ON ADIPOSE TISSUE AND BIOCHEMICAL PARAMETERS IN MALE OBESE WISTAR RATS - de Lima, D. G.; da Silva, C. F.; Freitas, A. G.; da Silva, O. L.P.; de Souza, F. M.A.; Bortolini, M. J.S.; Penha-Silva, N.; Santos, F. G.A.; de Carvalho, Y. K.; Valenti, Vitor E. [UNESP]; Silva, R. P.M. (ACTA Endocrinologica Foundation, 2021)
Context. Exercise and anabolic steroids are anticipated to promote fat mass reduction and so to decrease the number of comorbidities related to excessive weight. Objective. The aim of this study was to verify the influence of aerobic exercise and the use of steroids on the accumulation of adipose tissue and on the biochemical limitations of Wistar rats nourished by a hypercaloric diet. Methods. Forty, young male Wistar rats were split into four groups: obese control (n=10), obese under treatment (n=10), obese under aerobic exercise (n=10) and obese under aerobic exercise and treatment (n=10). All animals were fed with a hypercaloric diet and animals under treatment received intramuscular testosterone. Body (weight and visceral fat) and blood (lipidogram, glucose, and liver enzymes) parameters were assessed. Results. The group treated with aerobic exercise and testosterone revealed a reduction in body weight and visceral, perirenal, retroperitoneal and epididymal fats, accompanied by the blood levels of glucose, lactate, LDL-cholesterol, HDL-cholesterol, and lactate dehydrogenase; following high-intensity physical activity. Conclusion. The results support the theory that the combination of steroids and physical activity reduces the side-effects of androgenic-anabolic hormones and conveys benefits to some constraints.
Keywords: Cholesterol; Exercise; Obesity; Rats; Testosterone